ChatGPT’s Emerging Role in Dentistry: A Review - Mahantesh Achanur; Sumit Bhatt; Riddhi Nishit Maniyar; Arun Kumar Sajjanar; Aviroop Roy; Vinay Rao; Bharati Dewangan (Journal of Pharmacy and Bioallied Sciences)
This review examines the application of Chat generative pretrained transformer (ChatGPT), an advanced language model, in the field of dentistry. By analyzing its capabilities in patient communication, educational support, and diagnostic assistance, this study highlights the potential benefits of integrating artificial intelligence into dental practices. The review also addresses challenges such as ensuring accurate information, maintaining patient privacy, and integrating technology with existing dental workflows. With these insights, this paper concludes that ChatGPT can significantly enhance dental practices but requires careful consideration regarding ethical and practical implementation. Future research should focus on refining its application to maximize its positive impact on dentistry.